Lissencephaly, Pachygyrias, Band Heterotopias, RELN Pathway, and ARX Mutations (Incomplete Neuron Migration) - Sciuto, Laura; Fichera, Valeria; Zanghì, Antonio; Vecchio, Michele; Falsaperla, Raffaele; Galioto, Sebastiano; Palmucci, Stefano; Belfiore, Giuseppe; Di Napoli, Claudia; Polizzi, Agata; Praticò, Andrea D. (Journal of Pediatric Neurology, 2024)
Lissencephaly (LIS) is a group of malformations of cortical development consisting of a defective neuronal migration that results in lack of formation of the normal cerebral convolutions. It includes a spectrum of defect with varying degrees of severity, from agyria and pachygyria to subcortical band heterotopia. The etiopathogenesis of LIS includes both genetic and environmental factors. Although nongenetic forms of LIS have been reported, genetic causes are certainly more frequent and to date 19 LIS-SBH-associated genes have been identified. Most common mutations involve LIS1, DCX, ARX, and RELN genes. Clinically affected individuals present with early hypotonia, which can progress to limb spasticity, seizures, and psychomotor retardation. Convulsive episodes usually appear early (first months of life) and include infantile spasms, akinetic or myoclonic seizures, up to the development of complex epileptic syndromes, including atypical absences, myoclonia, and partial or tonic–clonic seizures. Several clinical entities are associated with classical LIS, including the following: isolated lissencephaly sequence (ILS); Miller–Dieker syndrome (MDS; OMIM 247200); subcortical band heterotopia (OMIM 300067); X-linked LIS with abnormal genitalia; and LIS with cerebellar hypoplasia. Diagnosis primarily depends on genetic and neuroimaging. Magnetic resonance imaging (MRI) is the gold standard, and it detects the presence of thick cortical cortex, its location, and the layers' architecture. Based on neuroimaging, it is possible to distinguish six subtypes of gyral malformations. Clinical and therapeutic management of these patients is challenging, considering the necessity to face drug-resistant epilepsy, intellectual disability, spasticity, and dysphagia and feeding problems. At the present moment, no gene-specific treatment for LIS is available.
Keywords: lissencephaly; pachygyria; brain malformation; genetics; syndromes